Social problems and patterns of juvenile delinquency in transitional Russia - Pridemore, William Alex (Journal of research in crime and delinquency, 2002)
This article is an introduction to social problems and juvenile delinquency in transitional Russia. Although crime in Russia is a popular topic of discussion in the popular press, there is relatively little work in the scholarly literature that directly addresses this issue and even less that examines juvenile delinquency in the country. This article is thus meant to be an introduction to this theme. The author reviews the current state of several institutions (such as the economy, education, and the family) as well as specific issues (such as alcohol and drug use, leisure activities, and the absence of a dedicated juvenile justice system in Russia) that are often thought to be related to juvenile delinquency and crime. The author then employs official data from the Russian Ministry of the Interior to describe the characteristics of young offenders in the country and the patterns of juvenile offending during the 1990s